Intellectual Capital Valuation of DSE-Listed Non-financial Companies in Bangladesh - Rana, Md. Sohel; Hossain, Syed Zabid (Archives of Business Research, 2023)
Intellectual capital (IC) is an organization's vital resource that helps the firm survive by confirming competitive edges. However, the valuation of IC resources is a challenging task. IC valuation is essential to employ the knowledge resource efficiently. Hence, the study aims to evaluate the IC resources of non-financial companies in Bangladesh and compare the IC performance between manufacturing and service firms. The study also explores the year-wise trend study and industry-based IC performance study. Data have been collected from secondary sources from 69 DSE-listed non-financial companies in Bangladesh from 2017 to 2021, comprising 345 company-year observations. The Modified Value Added Intellectual Coefficient (MVAIC) methodology has been adopted to reflect IC value. Independent Sample t-tests and graph and chart analyses have been performed to fulfill the study objectives. Results have shown that human capital is the primary driver of IC resources, and it dominates Intellectual Capital Efficiency (ICE) and then the overall IC efficiency (MVAIC) score. Human and structural resources utilized by Bangladeshi companies are better than those of relational and tangible capital. Service companies have better handled human and structural resources, but manufacturing companies have better used relational and employed capital. Research has also observed a declining trend of IC resources of the sampled companies. Telecommunication, Fuel and power, and Textile industries have better used IC resources. However, the tannery industry still needs to do so. The research contributes to resources-based theory by confirming the value of invisible resources, which supports business executives, policy-makers, managers, and potential and existing investors to make the right decisions. Further research may be conducted using an extended sample size, comparing financial and non-financial sectors or comparing among industries or valuation techniques like EVA, KCE, and CIV.